Exacerbated response to oxidative stress in the Retinitis Pigmentosa CerklKD/KO mouse model triggers retinal degeneration pathways upon acute light stress - Rocío García-Arroyo; Elena B. Domènech; Carlos Herrera-Úbeda; Miguel A. Asensi; Cristina Núñez de Arenas; José M. Cuezva; Jordi Garcia-Fernàndez; Federico V. Pallardó; Serena Mirra; Gemma Marfany (Redox Biology, 2023)
The retina is particularly vulnerable to genetic and environmental alterations that generate oxidative stress and cause cellular damage in photoreceptors and other retinal neurons, eventually leading to cell death. CERKL (CERamide Kinase-Like) mutations cause Retinitis Pigmentosa and Cone-Rod Dystrophy in humans, two disorders characterized by photoreceptor degeneration and progressive vision loss. CERKL is a resilience gene against oxidative stress, and its overexpression protects cells from oxidative stress-induced apoptosis. Besides, CERKL contributes to stress granule-formation and regulates mitochondrial dynamics in the retina. Using the CerklKD/KO albino mouse model, which recapitulates the human disease, we aimed to study the impact of Cerkl knockdown on stress response and activation of photoreceptor death mechanisms upon light/oxidative stress. After acute light injury, we assessed immediate or late retinal stress response, by combining both omic and non-omic approaches. Our results show that Cerkl knockdown increases ROS levels and causes a basal exacerbated stress state in the retina, through alterations in glutathione metabolism and stress granule production, overall compromising an adequate response to additional oxidative damage. As a consequence, several cell death mechanisms are triggered in CerklKD/KO retinas after acute light stress. Our studies indicate that Cerkl gene is a pivotal player in regulating light-challenged retinal homeostasis and shed light on how mutations in CERKL lead to blindness by dysregulation of the basal oxidative stress response in the retina.